Tax Avoidance and Firm Value: Moderating Role of Intellectual Capital - Abdullah Aziz Alaika; Eva Yunadia Chaerani; Muhammad Syauqi Fuqoha; Amrie Firmansyah (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study examines the effect of tax avoidance on the firm value by using intellectual capital as a moderating variable. The data used in this research is sourced from www.idnfinancials.com and www.idx.co.id, using data on financial statements and share prices of financial sector firms in the banking sub-sector listed on the Indonesia Stock Exchange for the period 2018 to 2021. This study employs a purposive sampling approach, so the total sample that can be used in this study is 128 observations. The test result suggests that tax avoidance is negatively associated with firm value. Also, this study finds that intellectual capital weakens the negative effect of tax avoidance on the firm value.